Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of silicon. Steel and cast iron: spectrophotometric method for silicon contents from 0.05% (m/m) to 1.0% (m/m) Part 3.26.3, (30th September 1987) - British Standards Institution,
No abstract available